PERILAKU AGRESIF PADA REMAJA DI LINGKUNGAN SEKOLAH MENENGAH ATAS WILAYAH URBAN DAN RURAL KABUPATEN JEMBER - M.Elyas Arif Budiman; Zidni Nuris Yuhbaba; Wahyi Sholihah Erdah Suswati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Aggressive as physical or verbal behavior intended to cause harm. Meanwhile, aggressive behavior is a serious problem that has a negative impact on adolescent mental health and achievement in school. The purpose of this study was to describe aggressive behavior in adolescents in high school environments in urban and rural areas of Jember Regency. The design of this research is a quantitative descriptive research. This research was conducted in senior high schools in rural and urban areas in Jember Regency with a total sample of 250 respondents who were selected using a purposive sampling method. This study used univariate analysis, wherein the results of this study will display demographic data and a description of aggressive behavior in adolescents. The results of the emotion study showed that 46.4% of respondents had verbally aggressive behavior, 29.6% of respondents had physically aggressive behavior, 12.8% of respondents had angry aggressive behavior and 11.2% of respondents had hostile aggressive behavior. Based on the results of this study that the aggressive behavior of adolescents tends to be high, so to overcome aggressive behavior in adolescents it is necessary to make various efforts by paying attention to the dimensions of development in adolescence so that the efforts developed are able to overcome various causes of mental health problems faced by adolescents and adolescents have resilience..